Strategi Penilaian Sikap Toleransi Mahasiswa dengan Mengintegrasikan Teknik Pete Ward dalam Pendidikan Teologi Berbasis Moderasi Beragama - Effendi, Muhamad Ridwan; Darma, Surya Hadi; Sa'dullah, Sa'dullah; Mardhiah, Izzatul; Azzahra, Salma (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
MulticulturalÂ theological education based on religious moderation is crucial in building a tolerant attitude among students. This study aims to develop an assessment of tolerance attitudes through the Liquid Ecclesiology approach proposed by Pete Ward. The methodology combines empirical methods based on concrete religious experience and theology. The multicultural theological education guide studied has five key elements: contemplation, reflection, construction, drafting proposals, and examining actions. This research was conducted at the State University of Jakarta and STAI DR. KH. EZ. Muttaqien focuses on Islamic theology courses for Islamic Religious Education study program students. The study results have produced a model of learning assessment instruments in Islamic Theology courses that include a commitment to nationality, rejection of violence, tolerance attitudes, and acceptance of local traditions to strengthen the spirit of tolerance in religious diversity for students.